Dynamic changes in atrial activation sequence during supraventricular tachycardia - Gülcü, Oktay; Merovci, Idriz; Tunçez, Abdullah; Kara, Meryem; Özcan Çetin, Elif Hande; Can, İrem Dilara; Kaplan, Elmas; Korkmaz, Ahmet; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Aras, Dursun; et al. (Wiley, 2022)
A29?year?old woman presented with repeated paroxysms ofpalpitations resulting from a rapid narrow QRS complex tachycar-dia (NCT). Her family and personal history were free of anycardiovascular pathology. After the initiation of an NCT following a1:2 ventricular response to programmed atrial stimulation(Figure1), a premature ventricular complex (PVC) from the rightparahisian region was delivered at a time when the His bundleactivation was completed (Figure2); subsequently, a dynamicchange in the retrograde atrial activation sequence (AAS) andventriculoatrial (VA) intervals were developed (Figure3). Based onthe findings within the figures, what is the mechanism of tachycardia?
Keywords: Accessory Pathway; Double Lop Tachycardia; Eccentric AVNRT; Electrophysiological Mechanism; Retrograde Atrial Activation Sequence; Supraventricular Tachycardia